Detecção de Listeria monocytogenes em leite: sensibilidade e especificidade de Reação em Cadeia de Polimerase (PCR) - Nadia David Peres (2007)
The aim of this work was to detect Listeria monocytogenes added in milk, after selectiveenrichment period, by PCR technique. A PCR technique using the primers LM1/LM2 and amultiplex PCR with IAP1/IAP2 e LMA/LMB was standardized. The conventional method of L.monocytogenes detection was compared from milk samples with different bacterial count addedwith various L. monocytogenes concentrations. The DNA extraction methods using phenolchloroformand thermal split were compared. The DNA extraction and the conventionalmethods showed the same result in detecting the bacterium in samples of sterilized milk. In milksamples with any initial contamination, the conventional methodology was sensitive and PCRfrom enrichment broth can not detect L. monocytogenes added, independently of the extractionmethod used. The identification time of L. monocytogenes decreased using the DNA extractionby the strain split method using suspect colonies that grew in Oxford and PALCAM, insubstitution of identification phenotypes tests